Isolation of a Volvariella diplasia hypercellulolytic auxotroph - and R.P. PHUTELA, M.S. SIDHU, H.S. SODHI (Indian Phytopathology, 2002)
V. diplasia Vd IIHR basidiospores were mutagenized using N-methyl-N-nitro-N-nitrosoguanidine to produce an adenine auxotroph Vd11. The enzyme production of the parent (Vd IIHR) and the mutant (Vd11) were compared, which revealed that the mutant was also an hypercellulolytic strain producing 0.71, 1.47 and 2.14 units/ml of total cellulase, endoglucanase and cellobiase, respectively. Of the C and N sources tested, cellulose and peptone formed the combination that gave maximum cellulolytic activity. The optimum incubation temperature for different components of the cellulase complex was 35deg C, while the pH range for different fractions of these enzymes was 5.0-6.0. It is concluded that a double mutant in V. diplasia was obtained, which was characterized as a stable hypercellulolytic adenine auxotroph.